A chitosan derivative-crosslinked hydrogel with controllable release of polydeoxyribonucleotides for wound treatment. (15th January 2023) - Sun, Yanzhen; Jing, Xiaodong; Liu, Yang; Yu, Bing; Hu, Hao; Cong, Hailin; Shen, Youqing
Abstract: Nucleic acid-based agents have advantages in therapeutic efficacy and biological safety. However, due to its facile degradability, it lacks an effective route of administration in wound treatment. Designing smart hydrogels for the spatiotemporally controllable delivery of nucleic acids is of great significance for clinical applications. Here, a near-infrared (NIR)-responsive nanocomposite hydrogel was prepared using methyl methacrylate (GMA)-modified chitosan as the macromolecular cross-linker, N-isopropylacrylamide (NIPAAm) as the backbone, and molybdenum disulfide nanosheets (MoS2 NSs) as the nanocomponents. The polydeoxyribonucleotide (PDRN), a nucleic acid-based agent that promotes tissue regeneration, was loaded and delivered. The photothermal conversion capability of MoS2 NSs enables customized care of PDRNs and antibacterial enhancement. In a full-thickness skin defect model, high-quality wound healing effects were demonstrated under the action of nanocomposite hydrogels. The proposed nanocomposite hydrogel provides a new reference for local delivery of nucleic acid-based agents. Graphical abstract: Unlabelled Image